Dependencies between indicators of the speed-power and balance stability of figure skaters - Yordanova, T.; Medvedeva, I.; Abele, A. (Journal of Physical Education and Sport, 2023)
Figure skating is a sport that combines endurance, strength, flexibility and grace with a touch of artistry. Since it is one of the early specialized sports monitoring training results and physical development, regularly performing and evaluating anthropometric measurements and fitness tests in and out of group comparisons can be useful for monitoring performance. One of the characteristics of modern figure skating is the progressive complexity of competitive programs. This process develops, in particular, in terms of the way athletes master elements and compounds of a rotational nature that are complex in terms of coordination, which is a strong irritant for the vestibular analyzer. The goal of this study is to determine the dependence between the speed-power capabilities and the indicators of equilibrium stability of figure skaters. The following tasks were set: measuring speed-force indicators with the "BTS G-sensor" equipment, measuring biomechanical dynamometric characteristics, and deriving correlation dependencies between speed-force indicators and balance stability. The correlation analysis of the sample test indicators involves analysis using multiple Pearson`s correlations. The indicators are biomechanical indicators, comprising kinematic, dynamic and equilibrium indicators. Intragroup correlation coefficients were present for the biomechanical characteristics of the kinematic and dynamic type, particularly for the squat jump type. A significant coefficient of correlation was found between speed-power qualities and indicators of vestibular stability in the type of bounce with the help of the arms (CMJA), which is an indicator of the coordination of movements. The results of the conducted studies allow us to consider that a decrease in the stability of the vestibular system of figure skaters occurs due to fatigue, as well as a decrease in the level of their special endurance. These data are to some extent explained by changes in the vestibular sensory system, which leads to the occurrence of technical errors when figure skaters participate in competitive programs.